2015
DOI: 10.1088/0004-637x/799/2/219
|View full text |Cite
|
Sign up to set email alerts
|

Chromospheric Rapid Blueshifted Excursions Observed With Ibis and Their Association With Photospheric Magnetic Field Evolution

Abstract: Chromospheric rapid blueshifted excursions (RBEs) are suggested to be the disk counterparts of type II spicules at the limb and believed to contribute to the coronal heating process. Previous identification of RBEs was mainly based on feature detection using Dopplergrams. In this paper, we study RBEs on 2011 October 21 in a very quiet region at the disk center, which were observed with the high-cadence imaging spectroscopy of the Ca ii 8542 Å line from the Interferometric Bidimensional Spectrometer (IBIS). By … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…If the generation mechanism is magnetic reconnection in the chromosphere (e.g. Shibata et al, 2007;Yurchyshyn, Abramenko, and Goode, 2013;Deng et al, 2015;Ni et al, 2015), it would indicate that there is no significant difference of magnetic structures in the chromospheric layers of CH and QS. In CH, it is probably small chromospheric loops that reconnect with open flux in the network.…”
Section: Resultsmentioning
confidence: 99%
“…If the generation mechanism is magnetic reconnection in the chromosphere (e.g. Shibata et al, 2007;Yurchyshyn, Abramenko, and Goode, 2013;Deng et al, 2015;Ni et al, 2015), it would indicate that there is no significant difference of magnetic structures in the chromospheric layers of CH and QS. In CH, it is probably small chromospheric loops that reconnect with open flux in the network.…”
Section: Resultsmentioning
confidence: 99%
“…as reconnection proceeds, the lower reconnected loops submerge below the solar surface, while the upper ones move upward and carry photospheric plasma with them. Presently, chromospheric jet-like events such as spicules/mottles (in the quiet Sun) 28,29 and fibrils (in ARs) 30 are investigated both through the latest generation of ground-based instruments, 31,32 together with the space-based observatories Hinode and Solar Dynamics Observatory. 33,34 Hinode observations of high-velocity spicules have recently revived the discussion on the contribution of these phenomena to coronal heating and solar wind generation.…”
Section: Waves and Heating Of The Solar Upper Atmospherementioning
confidence: 99%
“…33,34 Hinode observations of high-velocity spicules have recently revived the discussion on the contribution of these phenomena to coronal heating and solar wind generation. 32,34 However, the short observation times typically allocated to this type of observations on space observatories, due to the shared telemetry among different instruments, and the intrinsic limitations of ground-based observations, hamper further advances on this subject. Experimental confirmation of magnetic reconnection models requires high cadence observations of photospheric and chromospheric lines searching for cancelation of magnetic flux and plasma motions along the line of sight.…”
Section: Waves and Heating Of The Solar Upper Atmospherementioning
confidence: 99%
“…The use of imaging spectro-polarimeters (IBIS and CRISP) for disk observations has provided evidence that type-II spicules are readily observed on the solar disk as rapid variations in the far wings of Hα or Ca ii lines (so called RBEs, Langangen et al 2008;Sekse et al 2012;Kuridze et al 2015;Deng et al 2015). (Quasi-)simultaneous spectroscopy in these two lines has further shown that spicules (RBEs) undergo torsional motions and also that they might appear sequentially in lines formed at progressively higher temperature (Sekse et al 2013).…”
Section: Mhd Wavesmentioning
confidence: 99%
“…From disk observations of RBEs, they are reported to occur in small scale new magnetic concentrations in close proximity to network fields (Yurchyshyn et al 2013;Deng et al 2015), although the latter authors caution that an automatic approach recognizing both RBEs and magnetic cancellation yields a correlation with no better than random probability. A spicule-like jet appears in the 3D radiative-MHD simulation of Martínez-Sykora et al (2011), as due to a strong Lorentz force squeezing the chromospheric material and propelling the spicule along the magnetic field (see also Goodman 2014).…”
Section: Mhd Wavesmentioning
confidence: 99%